Expression of CYP3A4, CYP3A5 and CYP3A7 in human duodenal tissue - KIVISTÖ, KARI T.; BOOKJANS, GERHARD; FROMM, MARTIN F.; GRIESE, ERNST‐ULRICH; MÜNZEL, PETER; KROEMER, HEYO K. (British journal of clinical pharmacology, 1996)
The essential role of cytochrome P450 3A4 (CYP3A4) in human small intestine is well established, and CYP3A5 seems also to be present in most subjects. However, the role of CYP3A7 in the small intestine remains poorly characterized. We have therefore studied the expression of these CYP3A enzymes in the duodenal tissue from 19 patients, using a specific RT‐PCR (reverse transcriptase‐polymerase chain reaction) method. CYP3A4 and CYP3A5 were present at the mRNA level in the duodenum of 18 and 19 of the 19 patients studied, respectively. In contrast, mRNA for CYP3A7 was not found in the duodenum in any of the patients. These findings strongly suggest that, unlike CYP3A4 and CYP3A5, CYP3A7 is not expressed in human duodenum.